The Spread of Radical Understanding and Acts of Terrorism by the Al-Qaeda Network in Indonesia from a National Security Perspective - Kartika P, Seri Nenni; Priyanto Priyanto; Agus Adriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Terror acts carried out by the Al-Qaeda group and its network continue to occur in various countries, including Indonesia. The addition of group members to the network also shows existence over time. This condition is supported by the massive spread of radical ideology by the Al-Qaeda network, especially targeting educational environments and women. In this research, we want to outline the process of spreading radical ideology and the steps that need to be considered from a national security perspective. This research uses a qualitative descriptive method to explain the main discussion. The method used in data collection is secondary data obtained through literature study. The research results obtained are that emotional approaches, cultural factors, and the doctrine of wrong religious views, play an important role in the expansion of radical ideology, where groups of young people and women become victims as well as part of the perpetrators of the spread of radical ideology. Thus, the researcher provides suggestions and input for the Indonesian government in taking a gentle and persuasive approach as a step to minimize the spread of radical ideology in educational environments and among women. This step also aims to change the perspective of groups that have been exposed to radicalism.